2014
DOI: 10.1186/1471-2202-15-96
|View full text |Cite
|
Sign up to set email alerts
|

Functional two-way analysis of variance and bootstrap methods for neural synchrony analysis

Abstract: BackgroundPairwise association between neurons is a key feature in understanding neural coding. Statistical neuroscience provides tools to estimate and assess these associations. In the mammalian brain, activating ascending pathways arise from neuronal nuclei located at the brainstem and at the basal forebrain that regulate the transition between sleep and awake neuronal firing modes in extensive regions of the cerebral cortex, including the primary visual cortex, where neurons are known to be selective for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Indeed, NMDA increased LC network synchrony in our latter study, whereas no cross-correlation function estimate value could be quantified previously for any neuron during CNQX [ 27 ], as also found here for both AMPA and KA. Thus, a different type of (correlation) analysis needs to be applied in future studies testing AMPAR or KAR activation; e.g., activities of neuron pairs can be correlated as in other network synchrony studies [ 25 , 48 , 49 , 50 , 51 , 52 ]. Nevertheless, it can be concluded that TARP-AMPAR complex activation increases the phase-lock of LC spiking as both agonists decreased the LFP burst duration and single neuron spike jitter.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NMDA increased LC network synchrony in our latter study, whereas no cross-correlation function estimate value could be quantified previously for any neuron during CNQX [ 27 ], as also found here for both AMPA and KA. Thus, a different type of (correlation) analysis needs to be applied in future studies testing AMPAR or KAR activation; e.g., activities of neuron pairs can be correlated as in other network synchrony studies [ 25 , 48 , 49 , 50 , 51 , 52 ]. Nevertheless, it can be concluded that TARP-AMPAR complex activation increases the phase-lock of LC spiking as both agonists decreased the LFP burst duration and single neuron spike jitter.…”
Section: Discussionmentioning
confidence: 99%